Dukungan Orang Tua dalam Pencegahan Stunting pada Balita: Literatur Review - Julianto, Rahmad (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2024)
Parental support is important to maintain and encourage children's growth and development, especially at the age of five years. Stunting is a polemic for parents and an unavoidable problem, especially in developing countries such as Indonesia. Stunting is caused by chronic malnutrition and infections that occur at an early age of child growth and development. The purpose of this study is to analyze parental support in preventing stunting in toddlers. Studies with literature analysis conducted on the google scholar online database with accessible Indonesian text articles. The study results from seven articles analyzed various parental support in preventing stunting for their toddlers which are influenced by parental knowledge and awareness as well as positive behavior in supporting stunting prevention. The study findings investigate the need for parents' awareness and seriousness in providing support to maintain the nation's golden generation in the future.